2022
DOI: 10.1002/anie.202207310
|View full text |Cite
|
Sign up to set email alerts
|

Circularly Polarized Luminescence Active Supramolecular Nanotubes Based on PtIIComplexes That Undergo Dynamic Morphological Transformation and Helicity Inversion

Abstract: Circularly polarized luminescence (CPL) with tunable chirality is currently a challenging issue in the development of supramolecular nanomaterials. We herein report the formation of helical nanoribbons which grow into helical tubes through dynamic helicity inversion. For this, chiral PtII complexes of terpyridine derivatives, namely S‐trans‐1 and R‐trans‐1, with respective S‐ and R‐alanine subunits and incorporating trans‐double bonds in the alkyl chain were prepared. In DMSO/H2O (5 : 1 v/v), S‐trans‐1 initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 97 publications
2
9
0
Order By: Relevance
“…The time ( t 50 ) required to reach 50% of the maximum CD intensity (Δε 336 nm = 86 M –1 cm –1 ) was 5 min at c tot = 300 μM, which increased to 11.5 min upon decreasing the monomer concentration to 250 μM. This result reiterates that the nanotoroids directly organize into nanotubes without dissociation into monomers, i.e., the nanotoroids are intermediates on the pathway (on-pathway intermediates) to the formation of the nanotubes (Figure c). Similar non-linear growth of the CD signal was observed for scalemic (60% ee and 20% ee of 1R ) P -nanotoroids, albeit with relatively slow kinetics (Figure b). This observation suggests that the enantiomeric purity of the internal chiral side chains affects the interaction between the nanotoroids.…”
Section: Resultsmentioning
confidence: 68%
“…The time ( t 50 ) required to reach 50% of the maximum CD intensity (Δε 336 nm = 86 M –1 cm –1 ) was 5 min at c tot = 300 μM, which increased to 11.5 min upon decreasing the monomer concentration to 250 μM. This result reiterates that the nanotoroids directly organize into nanotubes without dissociation into monomers, i.e., the nanotoroids are intermediates on the pathway (on-pathway intermediates) to the formation of the nanotubes (Figure c). Similar non-linear growth of the CD signal was observed for scalemic (60% ee and 20% ee of 1R ) P -nanotoroids, albeit with relatively slow kinetics (Figure b). This observation suggests that the enantiomeric purity of the internal chiral side chains affects the interaction between the nanotoroids.…”
Section: Resultsmentioning
confidence: 68%
“…For example, previous research reported that the CPL of supramolecular assembly could be easily regulated by the exchange of metal ions. 39,40 Also, the CPL inversion of the metal organic supramolecular polymers (MOSPs) could be even achieved by tuning the content of metal ions. 41 However, compared with the extensive investigation of metal cations, the significance of anions in the assembly system with supramolecular chirality inversion is usually ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the dynamic and reversible property of noncovalent interactions, the chirality of supramolecular polymers in both the ground state and excited state , can be finely tuned and even inverted by various external stimuli. For example, previous research reported that the CPL of supramolecular assembly could be easily regulated by the exchange of metal ions. , Also, the CPL inversion of the metal organic supramolecular polymers (MOSPs) could be even achieved by tuning the content of metal ions . However, compared with the extensive investigation of metal cations, the significance of anions in the assembly system with supramolecular chirality inversion is usually ignored. In addition, temperature is an important external stimulus to influence the self-assembly pathway and modulate the chirality of supramolecular aggregates. For example, it is widely recognized that self-assembly in organic solvents is typically facilitated at lower temperatures due to the exothermic nature of the process by enthalpy .…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are an emerging class of crystalline materials composed of inorganic vertices (metal nodes or clusters) coordinated with organic struts (spacers) to form one-dimensional (1D), two-dimensional (2D), or three-dimensional (3D) architectures. , MOFs are widely regarded as a subtype of coordination polymers or coordination frameworks. Essentially, MOFs consist of open channels formed primarily by ejecting guest and terminal coordinated solvents through low-pressure heating. , Of the numerous porous materials reported to date, only a handful of examples show a much greater range of response to external stimuli than conventional materials. , Moreover, the activation of MOFs, which raises the energy state of these materials by eliminating the pore-filling solvent in the pore channels and the coordinating solvent that saturates the metal nodes, is an essential prerequisite for the use of MOFs in a variety of important structural applications, ranging from luminescence to molecular magnetism, , gas storage, gas or liquid separation, drug delivery, photocatalysis, electrocatalysis, , etc. Another industrially relevant application for which MOFs have shown promise is heterogeneous catalysis, , which is proving to be a versatile alternative to conventional inorganic materials, especially for a variety of organic oxidation processes.…”
Section: Introductionmentioning
confidence: 99%